A new species of Oneilliella from India with description of the female of Trachynotothrips brevispinis Masumoto & Okajima (Thysanoptera: Thripidae) - Singha, Devkant; Patidar, Abhishek; Tyagi, Kaomud; Kumar, Vikas (Zootaxa, 2021)
Oneilliella shivii sp.n. (Panchaetothripinae) is described from India as the second species in this genus. Trachynotothrips brevispinis and T. striatus (Thripinae) are newly recorded from India, and the first description provided of the female of T. brevispinis. Partial sequence data of mitochondrial cytochrome c oxidase (mtCOI) of these species were generated.